2016
DOI: 10.1038/ni.3466
|View full text |Cite
|
Sign up to set email alerts
|

Immunometabolism of regulatory T cells

Abstract: The bidirectional interaction between the immune system and whole-body metabolism has been well recognized for many years. Via effects on adipocytes and hepatocytes, immune cells can modulate whole-body metabolism (in metabolic syndromes such as type 2 diabetes and obesity) and, reciprocally, host nutrition and commensal-microbiota-derived metabolites modulate immunological homeostasis. Studies demonstrating the metabolic similarities of proliferating immune cells and cancer cells have helped give birth to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
256
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(265 citation statements)
references
References 86 publications
4
256
0
5
Order By: Relevance
“…Silencing of HIF1α in Tregs reverses these proinflammatory effects and restores their regulatory function (78). This direct modulation of the TH17/Treg balance marks HIF1α as an important director of T cell fate and immune effector functions (22,79).…”
Section: Hif1α and The Th17/treg Balancementioning
confidence: 98%
“…Silencing of HIF1α in Tregs reverses these proinflammatory effects and restores their regulatory function (78). This direct modulation of the TH17/Treg balance marks HIF1α as an important director of T cell fate and immune effector functions (22,79).…”
Section: Hif1α and The Th17/treg Balancementioning
confidence: 98%
“…During recent years, a growing number of studies have shown the importance of metabolic signals in immunity, the cellular metabolism dictates the fate and function of the immune cells (17)(18)(19)(20). To seek an effective treatment for sepsis, it will be helpful to elucidate metabolic process in the immune cells and analyze their metabolic changes in sepsis (20).…”
Section: The Metabolic Change Of Immune Cells In Sepsismentioning
confidence: 99%
“…Following pathogen invasion, the innate immune cells and T cells are activated and generate energy and essential components used in biosynthesis by switching metabolism from oxidative phosphorylation to aerobic glycolysis which is similar to the Warburg effect of tumor cells ( Figure 2) (18,21). Lipopolysaccharide (LPS) stimulation leads to an increase in the glycolytic process, while a decrease in mitochondria-dependent pyruvate oxidation and glutamine consumption, and fatty acid β-oxidation in monocytes/macrophages (22,23).…”
Section: The Metabolic Change Of Immune Cells In Sepsismentioning
confidence: 99%
See 1 more Smart Citation
“…An emerging example is the rise in obesity and its connection to T-cell biology [37], especially Tregs [38]. While obesity is a risk factor for a broad range of metabolic disorders, 3.6% of all new cancer cases worldwide are attributable to obesity [39].…”
mentioning
confidence: 99%